The long march to freedom [videorecording (DVD)] - Hill, Bernard, 1944- (Dreamscape Media, LLC, 2022)
The program tells the story of the thousands of British, American, and Commonwealth POWs who were forced to march from Poland to Germany in the winter of 1945.